Implementation of Tax Planning in Calculating Corporate Income Tax at BUMDes Raharjo, Batu City - Inggrid Solong; Gunawan, Cakti Indra; Risnaningsih (International Research & Development for Human Beings (IRDH), 2025)
One form of tax revenue that needs to be considered is the tax imposed on Village-Owned Enterprises (BUMDes). Village-Owned Enterprises (BUMDes) have a crucial role in advancing the economy in various villages in Indonesia with the aim of increasing the income and welfare of local communities, as well as increasing economic growth at the local level. In this research, corporate income tax taxpayers at BUMDes Raharjo Batu City in the Strawberry Barn Agriculture and Tourism Business Unit. The aim of this research is to determine tax planning in calculating corporate income tax at BUMDes Raharjo, Batu City. The research was conducted using descriptive qualitative methods. The data used are the results of direct interviews or with primary data from BUMDes Raharjo Batu City who were willing to be informants for the researcher and then recorded manually or with documentation by the researcher. The data analysis method used is exploratory descriptive analysis (descriptive non-statistical) by analyzing profit and loss reporting data and liability reports through formal and material aspects by studying aspects of income tax deductions related to BUMDes Raharjo, Batu City.